Mesta, chto o lenine nam govoryat, s velikoy lyubov'yu khranit leningrad. (Художник РСФСР)
Two paintings. One, a contemporary scenery of people visiting Lenin's hut in Leningrad (St. Petersburg). The other the same hut in the past Original title: места, что о ленине нам говорят, с великой любовью хранит ленинград. Suggested translation: The places that they tell us about Lenin are kept with great love by Leningrad. PO-2248